Le travail de l’écrit en coulisses de la relation de service - Jérôme Denis (Activités)
Services have been the subject of numerous studies by researchers who have highlighted the complex interactional work on which those services depend. This paper explores what goes on behind the scenes in order to shed light on the specific work that takes place within what the author terms “scriptural infrastructures” in the back office. It draws on an ethnographic study of the customer files processing department of a bank. Following a recent reorganisation, the employees’ work was cut off from the interactions that allowed the checking and completion of records with customers and was totally focused on the handling of various written documents. Observation shows that in these circumstances – and contrary to what management believes – reading and verifying records are anything but mechanical tasks. Both require the commitment of employees to conduct an inquiry through which they reduce, more or less easily, their doubts about the files, and they participate in the complex process of producing information that is gradually stabilized.